Flow structures on a planar food and drug administration (FDA) nozzle at low and intermediate reynolds number - Corrochano, Adrian; Xavier, Donnatella; Schlatter, Philipp; Vinuesa, Ricardo; Le Clainche, Soledad (Fluids, 2021)
In this paper, we present a general description of the flow structures inside a twodimensional Food and Drug Administration (FDA) nozzle. To this aim, we have performed numerical simulations using the numerical code Nek5000. The topology patters of the solution obtained, identify four different flow regimes when the flow is steady, where the symmetry of the flow breaks down. An additional case has been studied at higher Reynolds number, when the flow is unsteady, finding a vortex street distributed along the expansion pipe of the geometry. Linear stability analysis identifies the evolution of two steady and two unsteady modes. The results obtained have been connected with the changes in the topology of the flow. Finally, higher-order dynamic mode decomposition has been applied to identify the main flow structures in the unsteady flow inside the FDA nozzle. The highest-amplitude dynamic mode decomposition (DMD) modes identified by the method model the vortex street in the expansion of the geometry.
CRIS-Team Scopus Importer:2023-03-21
Keywords: FDA nozzle; Flow structures; Higher order dynamic mode decomposition; Linear stability analysis